454-Pyrosequencing analysis of highly adapted azo dye-degrading microbial communities in a two-stage anaerobic–aerobic bioreactor treating textile effluent. Issue 6 (19th March 2017) - Köchling, Thorsten; Ferraz, Antônio Djalma Nunes; Florencio, Lourdinha; Kato, Mario Takayuki; Gavazza, Sávia
ABSTRACT: Azo dyes, which are widely used in the textile industry, exhibit significant toxic characteristics for the environment and the human population. Sequential anaerobic–aerobic reactor systems are efficient for the degradation of dyes and the mineralization of intermediate compounds; however, little is known about the composition of the microbial communities responsible for dye degradation in these systems. 454-Pyrosequencing of the 16S rRNA gene was employed to assess the bacterial biodiversity and composition of a two-stage (anaerobic–aerobic) pilot-scale reactor that treats effluent from a denim factory. The anaerobic reactor was inoculated with anaerobic sludge from a domestic sewage treatment plant. Due to the selective composition of the textile wastewater, after 210 days of operation, the anaerobic reactor was dominated by the single genus Clostridium, affiliated with the Firmicutes phylum. The aerobic biofilter harbored a diverse bacterial community. The most abundant phylum in the aerobic biofilter was Proteobacteria, which was primarily represented by the Gamma, Delta and Epsilon classes followed by Firmicutes and other phyla. Several bacterial genera were identified that most likely played an essential role in azo dye degradation in the investigated system.